Practice patterns for deep vein thrombosis prophylaxis in minimal-access surgery - Beekman, Richard (Canadian Medical Association, 2006)
BACKGROUND: There are no comprehensive evidence-based guidelines for deep vein thrombosis (DVT) prophylaxis in patients undergoing minimal-access surgery (MAS). METHODS: We completed a cross-sectional survey of general surgeons practising in Ontario, in order to establish current practice patterns for DVT prophylaxis for MAS procedures. RESULTS: The mean duration of practice of respondents was 15.4 years, with most (67.0%) practising outside an academic centre. For minor MAS, most surgeons do not give DVT prophylaxis (73.8% in laparoscopic cholecystectomy and 63.7% in laparoscopic inguinal hernia repair). For major MAS, a minority of surgeons do not give DVT prophylaxis (4.1% in laparoscopic colorectal surgery and 13.6% in laparoscopic splenectomy). However, there remains considerable variation in the mechanism (pharmacological, mechanical), approach and duration (perioperative, postoperative) of DVT prophylaxis among respondents in all case scenarios evaluated. Academic surgeons and surgeons in practice for 15 years or less are more aggressive with preoperative heparin administration. CONCLUSIONS: There is substantial and important variability in the current practice of general surgeons with respect to DVT prophylaxis for MAS. Considerable benefit will be derived from clinical trials that provide data to establish appropriate DVT prophylaxis guidelines for MAS.